Approaching the forensic significance of possible PMMR correlates in a case of assumed cardiac rigor mortis. (June 2020) - Saitou, Hajime; Shiotani, Seiji; Kobayashi, Tomoya; Hayakawa, Hideyuki
Abstract : PMMR imaging may delineate a correlate for assumed cardiac rigor mortis, which seems to be practically impossible to reliably identify macroscopically. The main finding in this case is a concentric ring showing lower SI on T2WI in the PMMR imaging of the subendocardial region of the left ventricle. The assumed effect of cardiac rigor mortis appears to dominate the PMMR signal by reducing free watery fluid rather than by increasing fluid viscosity or halting flow rate. T2WI of PMMR imaging in our study depicted the cardiac rigor mortis as low SI in the subendocardial region. T2 blackout effect suggests that the low SI on DWI was caused by the low SI on T2WI. Abstract: We demonstrate a left ventricular subendocardial ring as low signal intensity (SI) findings in a T2-weighted image (T2WI) sequence in postmortem magnetic resonance (PMMR) imaging. As plausible explanation, we propose rigor mortis of the heart muscle and discuss the implications of that. An 18-year-old man with a previous history of arrhythmia suddenly went into cardiopulmonary arrest while eating. Although cardiopulmonary resuscitation was performed for 120 min, death was confirmed. Autopsy revealed the cause of death to be sudden cardiac death due to arrhythmia induced by arrhythmogenic right ventricular cardiomyopathy. In this case, PMMR imaging performed before autopsy demonstrated a low SI area in the subendocardial region, suggesting a cardiac rigor mortis on the short-axial T2WI, apparent diffusion coefficient (ADC) map, and diffusion-weighted image (DWI). Low SI on T2WI is considered to be lesser interstitial fluids distribution in more-pressured subendocardial region, low SI on ADC map to be higher viscosity in subendocardial region, and low SI on DWI to be T2 blackout effect. PMMR imaging may delineate a correlate for assumed cardiac rigor mortis, which seems to be practically impossible to reliably identify macroscopically.